Tingkat Serangan dan Musuh Alami Spodoptera frugiperda Je. Smith pada Tanaman Jagung di Lima Kecamatan di Kabupaten Banyumas - Agus Suroto; Loekas Soesanto; Ni Wayan Anik L; Muhamad Bahrudin (UM Purwokerto Press, 2021)
The survey of the distribution and damage of the new pest Spodoptera frugiperda is an important activity to determine appropriate control measures. In addition, the search for natural enemies is also needed as an alternative to controlling these pests. The purpose of this study was to determine the level of damage and the types of natural enemies found in several locations in Banyumas Regency. The method used is perposive random sampling in Banyumas Regency in five sub-districts, namely Ajibarang, Baturaden, Gumelar, Kedungbanteng, and Sumpiuh. Observations were made at 08.00-11.00 WIB from March to June 2021. The results showed that the attack rate of Spodoptera frugiperda larvae varied at each observation location. The highest attack rate was in Sumpiuh and Gumelar Districts, followed by Ajibarang, Kedungbanteng and Baturaden Districts. One species of parasitoid was found, namely Apanteles sp. and 9 predators, namely Oxyopes salticus, Dermaptera, Holcocephala sp., Rainieria sp., Orius insidiosus, Dolichoderus sp., Paratrechina sp., Oecophylla sp. and Conocephalus longipennis. At the individual paraistoid level, Apanteles sp. became the most common, followed by the predatory fly Holcocephala sp. and ants Dolichoderus sp., fly Rainieria sp., ladybug Orius insidiosus, Dermaptera, ant Paratrechina sp., ant Oecophylla sp. and the grasshopper Conocephalus longipennis.